Analisis Perilaku Kerja Pegawai Kelurahan Nagasari Karawang - Apriyanti A; Uus MD Fadli (Yayasan Daarul Huda Kruengmane, 2023)
The development of statistics has a role to provide accurate results on work behavior in managing its resources. Work behavior is very important, because it is part of a person's function involved in an action which is a response or reaction to a stimulus. The purpose of this study is to analyze the work behavior of employees when working and serving the Nagasari village community and realigning the vision and mission of employee performance so that they can realize the ideals of Nagasari village. This study used a qualitative approach with descriptive methods, in conducting this research using survey techniques (observation or direct field work) and interview techniques, interviews were conducted to obtain problems from a number of informants consisting of 8 Nagasari sub-district employees. The results achieved from this study can improve the work behavior of Nagasari sub-district employees. It can be concluded that the Nagasari sub-district is quite good in work behavior and the employees have carried out work-related obligations. As for things that can be used as input for the Nagasari sub-district office, namely the importance of increasing employee capabilities through an analysis of the work behavior of Nagasari sub-district employees contained in the sub-district program.